Six years of continuous carbon isotope composition measurements of methane in Heidelberg (Germany) - a study of source contributions and comparison to emission inventories - Hoheisel, Antje; Schmidt, Martina (Atmospheric chemistry and physics, 2024)
Mitigation of greenhouse gases requires a precise knowledge of their sources at both global and regional scales. With improving measurement techniques, in situ δ(13C,CH4) records are analysed in a growing number of studies to characterise methane emissions and to evaluate inventories at regional and local scales. However, most of these studies cover short time periods of a few months, and the results show a large regional variability. In this study, a 6-year time record of in situ δ(13C,CH4), measured with a cavity ring-down spectroscopy (CRDS) analyser in Heidelberg, Germany, is analysed to obtain information about seasonal variations and trends of CH4 emissions. The Keeling plot method is applied to atmospheric measurements on different timescales, and the resulting source contributions are used to evaluate the CH4 emissions reported by two emission inventories: the Emissions Database for Global Atmospheric Research (EDGAR v6.0) and the inventory of the State Institute for the Environment Baden-Württemberg (LUBW). The mean isotopic carbon source signature for the Heidelberg catchment area derived from atmospheric measurements is (-52.3±0.4) ‰ and shows an annual cycle with 5.8 ‰ more depleted values in summer than in winter. This annual cycle can only be partly explained by seasonal variations in the 13C-enriched emissions from heating and reveals strong seasonal variations in biogenic CH4 emissions in the Heidelberg catchment area, which are not included in EDGAR v6.0. The comparison with emission inventories also shows that EDGAR v6.0 overestimates the CH4 emissions from less depleted sources. In situ CH4 isotope analysers at continental and urban monitoring stations can make an important contribution to the verification and improvement of emission inventories.